In vitro Production of IL-6 and IFN-γ is Influenced by Dietary Variables and Predicts Upper Respiratory Tract Infection Incidence and Severity Respectively in Young Adults - Meng, Huicui; Lee, Yujin; Ba, Zhaoyong; Fleming, Jennifer A.; Furumoto, Emily J.; Roberts, Robert F.; Kris-Etherton, Penny M.; Rogers, Connie J. (Frontiers in Immunology, 2015)
Assessment of immune responses in healthy adults following dietary or lifestyle interventions is challenging due to significant inter-individual variability. Thus, gaining a better understanding of host factors that contribute to the heterogeneity in immunity is necessary. To address this question, healthy adults (n=36, 18-40 years old, BMI 20-35 kg/m2) were recruited. Dietary intake was obtained via 3-day dietary recall records, physical activity level was evaluated using the IPAQ questionnaire, and PBMCs were isolated from peripheral blood. Expression of activation markers on unstimulated immune subsets was assessed by flow cytometry. T cell proliferation and cytokine secretion was assessed following in vitro stimulation with anti-CD3 or LPS. Furthermore, the incidence and severity of cold or flu symptoms were obtained from self-reported URTI questionnaires. The relationship between activation marker expression on T cells and T cell effector functions; and in vitro cytokine secretion and URTI was determined by linear or logistic regression. CD69 and CD25 expression on unstimulated T cells was significantly associated with T cell proliferation and IL-2 secretion. Incidence and severity of cold or flu symptoms was significantly associated with in vitro IL-6 and IFN-γ secretion, respectively. Furthermore, host factors (e.g. age, BMI, physical activity, and diet) contributed significantly to the relationship between activation marker expression and T cell effector function, and cytokine secretion and cold and flu status. In conclusion, these results suggest that lifestyle and dietary factors are important variables that contribute to immune responses and should be included in human clinical trials that assess immune endpoints.